2004
DOI: 10.1002/ejic.200400059
|View full text |Cite
|
Sign up to set email alerts
|

The Hybrid Organic‐Inorganic 2‐D Material (CsNa2[{Sn(CH3)2}3(H2O)4(β‐XW9O33)]·7H2O) (X = AsIII, SbIII) and Its Solution Properties

Abstract: We report on the hybrid organic-inorganic 2-D materials (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…In addition to the results we have already published (see ref. [18]) and the structure presented herein, we have several other discrete and also polymeric polyanion structures with completely unprecedented geometries. These results will be published elsewhere.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to the results we have already published (see ref. [18]) and the structure presented herein, we have several other discrete and also polymeric polyanion structures with completely unprecedented geometries. These results will be published elsewhere.…”
mentioning
confidence: 93%
“…We have already demonstrated that this electrophile can be incorporated in lone-pair-containing polyanion precursors. [18] Furthermore, we have discovered that the two organic groups are always trans to each other, which allows the construction of large polyanions with unexpected geometries. Herein we report the reactivity of dimethyltindichloride with the trilacunary Keggin precursors [A-XW 9 O 34 ] 9À (X = P, As).…”
mentioning
confidence: 99%
“…The choice of the dual combination, electrophilic linker/nucleophilic POM unit, represents a key parameter for the targeted geometry of the resulting assembly. The control of the design can be achieved using an electrophilic linker with reduced coordinative requirement as exemplified by Kortz et al using the dimethyltin cation {SnMe 2 } 2+ where four equatorial coordination sites are available [45][46][47][48][49]. The length of the linker can be increased, for example by using the dinuclear unit {Mo 2 O 2 S 2 } 2+ , which permits to enlarge the size of the resulting modular species [50].…”
Section: Introductionmentioning
confidence: 99%